The relationship between foreign direct investment, financial development and growth economic in Next-11 Countries: a PMG/ ARDL estimation - Louail, Bilal; Zouita, Mohamed Salah (Zielona Góra: Faculty of Economics and Management Press)
This study investigates the relationship between FDI, economic growth and financial development in the Next 11 countries. An analysis of the results was performed accordingly on the panel data gathered from the Next 11 countries from 1985 to 2019 - using the Pooled Mean Group (PMG) estimation method and the Autoregressive Distributed Lag model approach (ARDL).
Keywords: foreign direct investment; financial development; growth economic; Next-11 countries; bezpośrednie inwestycje zagraniczne; inwestycje zagraniczne; rozwój finansowy; wzrost gospodarczy; kraje grupy Next-11; Next-11